E-LEARNING MEDIA AS LEARNING RESOURCES IN STATE UNIVERSITY OF MALANG - Desti Nur Aini; Sawitri Retnantiti; Dudy Syafrudin (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2017)
This study aimed to describe (1) the use of e-learning UM Student in State Univesitu of Malang as a learning media, (2) provision of material by lecturers in the classroom, and (3) the problems in the use of e-learning., Evaluative quantitative research approach used in this study. The quantitative research methods focuses on more things that can be measured by numbers or quantifiable. The evaluative research focused on the final recommendations of evaluation. It confirms that an object can be maintained, upgraded, improved, or even dismissed with the data. The population in this study is a student of German Literature, Faculty of Letters State University of Malang (UM) and restricted to students in class of 2013, 2014 and 2015. The research instrument used in this study using a questionnaire. The results showed that (1) the use of e-learning has been empowered with quite well by the students of German Literature, Faculty of Letters State University of Malang (UM), although the frequency of media use is still not maximized. The intensity of the use of e-learning is still low (the answer "seldom" by students) is due to lack of motivated students in utilizing of e-learning media. The use of e-learning UM obtained only teaching materials. The use of e-learning was less in terms of frequency of use, either to find information and get a learning material. (2) Providing material by the lecturers  are already quite varied. It can be seen by (a) the provision of handouts / modules / video learning through e-learning media, (b)  more (often) assignment / exercise, (c) the majority of references is available, and (d) always opens the opportunity to ask questions and discuss. (3) The problems caused by (a) the display is too formal; (B) the use of navigation is not clear; (C) maintenance disorder that happens sometimes; and (d) ignorance of the students on the use of certain features.Keywords: E-learning in State University of Malang (UM) , learning resources, student